2019
DOI: 10.1149/2.0971902jes
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Film-Forming Additive in Ionic Liquid Electrolyte on Electrochemical Performance of Si Negative-Electrode for LIBs

Abstract: 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)amide (EMI-TFSA) is one of the promising ionic liquids as electrolyte solvent to enhance the electrochemical performance of Si electrode for Li-ion batteries (LIBs) because of its low viscosity and high conductivity. However, it has low stability against reduction and its reductive decomposition product inhibits Li + insertion to electrodes, leading to poor cycling stability. To exert a potential of EMI-TFSA, we employed vinylene carbonate (VC) as film-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…Examples of ILs that have been identified as suitable electrolytes include: ammonium , pyridinium [47][48][49][50], piperidinium , imidazolium [78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97] and pyrrolidinium. Each cation offers favorable properties, for example, piperidinium ionic liquids possesses non-flammability, large electrochemical window (−3.8 to 2.5 V vs. Pt) [98], and inherent conductivity, which make them suitable for use as an electrolyte solvent in electrical energy storage devices [51,52].…”
Section: Ionic Liquids (Il) For Energy Storage Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of ILs that have been identified as suitable electrolytes include: ammonium , pyridinium [47][48][49][50], piperidinium , imidazolium [78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97] and pyrrolidinium. Each cation offers favorable properties, for example, piperidinium ionic liquids possesses non-flammability, large electrochemical window (−3.8 to 2.5 V vs. Pt) [98], and inherent conductivity, which make them suitable for use as an electrolyte solvent in electrical energy storage devices [51,52].…”
Section: Ionic Liquids (Il) For Energy Storage Applicationsmentioning
confidence: 99%
“…Extensive research has been carried out on 1-ethyl-3-methylimidazolium-based ILs. This IL has shown compatibility with a wide range of cathode and anode materials in both its liquid [ 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 ] and polymer gel form [ 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 ]. Other imidazolium-based ILs have been synthesized and characterized, and their physicochemical properties were determined [ 108 , 109 , 110 ].…”
Section: Ionic Liquids (Il) For Energy Storage Applicationsmentioning
confidence: 99%
“…This observed lithiated/delithiated profiles were agreement with that of the majority of Si anodes reported. [13][14][15][16][17] This suggested that the lithiation reaction of Si/ CyDC-SA included not only the insertion reaction of Li into carbon but also the alloying reaction between Li and Si. The Si utilization factor in the lithiation/delithiation process was calculated to be 26% of Si nanoparticles contained in Si/CyDC-SA.…”
Section: Characterization and Electrochemical Properties Of The Obtaimentioning
confidence: 99%
“…The wide electrochemical window of the ionic liquid can broaden the working voltage of the LIBs [21][22][23]. Ionic liquids as electrolyte additives are known to enhance the electrochemical performance of lithium ion batteries (LIBs) [24][25][26][27][28][29][30][31]. Therefore, the problem of high-voltage oxidative decomposition is expected to be solved by using ionic liquid electrolyte additive [32][33][34].…”
Section: Introductionmentioning
confidence: 99%